STRUKTUR KEPEMILIKAN DAN AGRESIVITAS PAJAK - Marcelino Chandra Rusli; Mulyani Mulyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Tax is a State taxpayer contribution that must be paid by an individual or entity that has a firm nature. Many taxpayers, especially large corporations, are trying to minimize their tax burden. One phenomenon that often occurs is companies that carry out tax avoidance and income distribution in order to pay a small tax burden in order to obtain high profits. This study aims to determine the effect of family ownership, foreign ownership, concentrated ownership, managerial ownership, and institutional ownership on tax aggressiveness in companies. Tax aggressiveness is tax planning either by way of avoidance or by tax evasion. Factors that make the ownership structure perform tax aggressiveness is dominant ownership in a company that can control the company's management for personal gain. In this study, tax aggressiveness is proxied by using the effectiveness tax rate (ETR). The sample selection in this study used a purposive sampling method. The results of this study are (1) family ownership has no evidence of tax aggressive, (2) foreign ownership is proven to influence tax aggressiveness, (3) concentrated ownership has no evidence of tax aggressive, (4) managerial ownership has no evidence of tax aggressive, (5) institutional ownershipis has no evidence of tax aggressiveness.